Competitive adsorption of pharmaceuticals in lake water and wastewater effluent by pristine and NaOH-activated biochars from spent coffee wastes: Contribution of hydrophobic and π-π interactions. (1st February 2021) - Shin, Jaegwan; Kwak, Jinwoo; Lee, Yong-Gu; Kim, Sangwon; Choi, Minhee; Bae, Sungjun; Lee, Sang-Ho; Park, Yongeun; Chon, Kangmin
Abstract: This study investigated the competitive adsorption mechanisms of pharmaceuticals (i.e., naproxen, diclofenac, and ibuprofen) toward the pristine and NaOH-activated biochars from spent coffee wastes (SCW) in lake water and wastewater effluent. The kinetic and isotherm studies revealed that the improved physicochemical characteristics and physically homogenized surfaces of the pristine SCW biochar through the chemical activation with NaOH were beneficial to the adsorption of pharmaceuticals (competitive equilibrium adsorption capacity (Qe, exp ): NaOH-activated SCW biochar (61.25–192.07 μmol/g) > pristine SCW biochar (14.81–20.65 μmol/g)). The adsorptive removal of naproxen (Qe, exp = 14.81–18.81 μmol/g), diclofenac (Qe, exp = 15.73–20.00 μmol/g), and ibuprofen (Qe, exp = 16.20–20.65 μmol/g) for the pristine SCW biochar showed linear correlations with their hydrophobicity (log D at pH 7.0: ibuprofen (1.71) > diclofenac (1.37) > naproxen (0.25)). However, their Qe, exp values for the NaOH-activated SCW biochar (naproxen (176.39–192.07 μmol/g) > diclofenac (78.44–98.74 μmol/g) > ibuprofen (61.25–80.02 μmol/g)) were inversely correlated to the order of their log D values. These results suggest that the reinforced aromatic structure of the NaOH-activated SCW biochar facilitated the π-π interaction. The calculated thermodynamic parameters demonstrated that the competitive adsorption of pharmaceuticals on the NaOH-activated SCW biochar compared to pristine SCW biochar occurred more spontaneously over the entire pH (5.0–11.0) and ionic strength (NaCl: 0–0.125 M) ranges. These observations imply that the NaOH-activated SCW biochar might be potentially applicable for the removal of pharmaceuticals in lake water and wastewater effluent. Graphical abstract: Image 1 Highlights: Competitive adsorption of pharmaceuticals investigated under real water matrices. NaOH-activated SCW biochar has high specific surface area and total pore volume. NaOH-activated SCW biochar eliminates NPX, DCF, and IBU more effectively. Adsorption of pristine SCW biochar corresponds to Log D values of micropollutants. Increased aromaticity of NaOH-activated SCW biochar stimulates π-π interaction.